Metal and Nutrient Transporters in Abiotic Stress - Roychoudhury M.Sc., Ph.D., Aryadeep; Roychoudhury M.Sc., Ph.D., Aryadeep; Tripathi D. Phil., Durgesh Kumar; Deshmukh, Rupesh (Academic Press, 2021)
Metal and Nutrient Transporters in Abiotic Stress focuses on the different forms of environmental stress related to heavy metal, metalloid and nutrient deficiency that have the potential to inflict major damages to crop plants, leading to a massive decrease in crop yield and productivity. The book presents the current state of knowledge of the biochemical and molecular regulation of several classes of membrane transporters related to the uptake of metals/metalloids and nutrient elements during different stresses and their probable mechanisms of operation in plant stress tolerance. Metal and Nutrient Transporters in Abiotic Stress provides a comprehensive discussion that will help in mitigating multiple forms of stresses utilizing transporter proteins. Edited by leading experts and written by a global team of knowledgeable contributors, this book will further stimulate research in the field of transporter proteins and will foster further interests for researchers, academicians and scientists worldwide. It is complimented by its companion book titled Transporters and Plant Osmotic Stress. - Focuses exclusively on metal and nutrient transporters involved in multiple environmental stresses in plants - Explains exploiting transporters in crop improvement programs through transgenic technology against different stresses such as heavy metal, metalloid and nutrient deficiency - Serves as an important source of information in the field of abiotic stress